Learning to ‘be’ a university student: First in family students negotiating membership of the university community - Groves, Olivia; O'Shea, Sarah (ELSEVIER SCI LTD, 2019)
An integral part of the higher education (HE) journey is the act of ‘becoming’ a student, however students who are first in their families (FiF) to attend university have had limited exposure to the HE environment. Innovatively for research with this cohort, this paper draws on situated learning theory to examine how learning to become a university student occurs through participation within the university community of practice. Drawing upon in-depth interviews with FiF learners at the end of their degrees, i.e. successful students, the analysis describes students’ movement from initial participation at the periphery of the university community to fuller participation. This paper offers practical insights into how we might support and engage this cohort to improve student retention.